MXene doping-based polycarbonate conductive elastomer as well as preparation method and application thereof

By doping polycarbonate conductive elastomers with MXene to form a stable cross-linked network, the problems of conductivity, tensile strength, multifunctionality, and interface stability are solved, resulting in a high-performance conductive elastomer material suitable for a variety of applications.

CN120988448AActive Publication Date: 2025-11-21NINGDE NORMAL UNIV
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202511530709.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-24
Publication Date
2025-11-21
Estimated Expiration
2045-10-24

AI Technical Summary

Technical Problem

Existing conductive elastomers have shortcomings in balancing conductivity and tensile strength, multifunctional integration and interfacial stability, and their preparation methods are complex and difficult to meet the needs of industrial production.

Method used

MXene-doped polycarbonate conductive elastomers are used. By doping MXene into aliphatic polycarbonate and polydeuterium solvent, a stable cross-linking network is formed. Combined with abundant multiple hydrogen bonding, the mechanical properties, electrical response characteristics and photothermal antibacterial function of the material are improved.

Benefits of technology

It achieves improved structural stability and mechanical properties of materials, excellent sensing sensitivity, significant photothermal conversion capability, and highly efficient antibacterial properties, making it suitable for fields such as flexible sensors, electronic skin, and health monitoring.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120988448A_ABST
    Figure CN120988448A_ABST
Patent Text Reader

Abstract

The invention provides a polycarbonate conductive elastomer based on MXene doping and a preparation method and application thereof, the conductive elastomer comprises aliphatic polycarbonate (APC), a deep eutectic solvent (PDES) and MXene, the mass ratio of the aliphatic polycarbonate to the deep eutectic solvent is 1: 0.5-3, and the addition amount of the MXene is 1-5 wt% of the total mass of the APC and the PDES. The conductive elastomer obtained by the invention is simple in preparation process, environment-friendly and free of high temperature and high pressure; the comprehensive performance of mechanical strength, electrical sensitivity, biocompatibility and degradability, photo-thermal response and antibacterial performance is realized; the material is stable in structure and suitable for the fields of flexible sensors, electronic skin, health monitoring, photo-thermal therapy, intelligent antibacterial materials and the like.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the technical field of flexible functional materials, and particularly relates to a polycarbonate-based conductive elastomer based on MXene doping and a preparation method and application thereof. BACKGROUND

[0002] In recent years, with the rapid development of flexible electronic technology, intelligent wearable devices and artificial intelligence sensing systems, higher requirements have been put forward for new conductive materials with high flexibility, high sensitivity, excellent response performance and multifunctional integration. Traditional rigid sensors have been unable to meet the comprehensive demand for flexibility, stretchability, reusability and multifunctionality of wearable devices, miniaturized biomedical devices, intelligent skin and the like. Therefore, developing a conductive elastomer material that has good mechanical properties, conductive properties and other additional functions (such as antibacterial, photothermal response, etc.) has become one of the important research directions in the field of high polymer materials and flexible electronics.

[0003] Conductive elastomer refers to a composite material that is endowed with certain conductive ability by doping conductive fillers (such as metal nanoparticles, carbon-based nanomaterials, conductive polymers, etc.) in a flexible high polymer material matrix. It not only retains the softness and stretchability of elastomers, but also introduces conductive paths, so that it can respond to external mechanical stimuli and is widely used in flexible sensors, electronic skin, artificial muscles, intelligent robots and the like. However, the current research and development of conductive elastomers faces the following technical problems: (1) difficulty in balancing conductivity and stretchability: generally speaking, increasing the content of conductive fillers helps to improve the electrical conductivity of the composite material, but too high filler will make the material brittle and lose elasticity, thereby weakening its stretchability and mechanical stability, limiting its application in wearable devices. (2) Insufficient multifunctional integration: many current conductive elastomers only have conductivity and certain flexibility, lack of functions such as photothermal response, antibacterial, sensing programmable, etc., which is not conducive to their promotion in biomedical, intelligent health and other complex application scenarios. (3) Poor interface stability: due to the poor interface compatibility between inorganic conductive fillers and organic polymer matrix, phase separation or filler shedding may occur during the strain process, leading to damage to the conductive network and performance degradation. (4) Complex structure construction method, large industrialization difficulty: the construction of many existing conductive elastomers relies on high-energy consumption, high-pollution or low-efficiency preparation methods, which cannot meet the needs of large-scale industrial production. SUMMARY

[0004] The present application is carried out in view of the above-mentioned problems, and aims to provide a multifunctional conductive elastomer based on MXene doping and a preparation method and application thereof. The elastomer material not only has good flexibility and mechanical strength, but also has high electrical sensitivity, excellent photothermal response ability and high-efficiency antibacterial performance, and is suitable for fields such as smart wear, flexible sensors, biomedical patches and the like.

[0005] In order to achieve the above-mentioned purpose, the present application provides a multifunctional conductive elastomer based on MXene doping, which has excellent mechanical properties, electrical response characteristics, biocompatibility, biodegradability and photothermal antibacterial function.

[0006] The first aspect of the present application provides a polycarbonate-based conductive elastomer based on MXene doping, which comprises aliphatic polycarbonate (APC), polydeep eutectic solvent (PDES) and MXene, the mass ratio of the aliphatic polycarbonate and the polydeep eutectic solvent is 1:0.5-3, and the addition amount of the MXene is 1-5 wt% of the total mass of the APC and the PDES.

[0007] In any embodiment, the aliphatic polycarbonate is prepared from the following raw materials: polyethylene glycol monomethyl ether, 5-methyl-5-benzyloxycarbonyl trimethylene carbonate, 5-methyl-5-carboxyl trimethylene carbonate and stannous octoate, and the mass ratio of the substances is 1:50:25-50:1.

[0008] In any embodiment, the polydeep eutectic solvent is prepared from the following raw materials: choline chloride and acrylic acid, and the mass ratio of the substances is 1:1-2.

[0009] The second aspect of the present application further provides a preparation method of a polycarbonate-based conductive elastomer based on MXene doping, which comprises the following steps: 1) Synthesis of aliphatic polycarbonate; 2) Synthesis of polydeep eutectic solvent; 3) Pre-mixing and dissolving: APC and PDES are weighed and added to N,N-dimethylformamide at a mass ratio of 1:0.5-3, and magnetic stirring is carried out at 50-100℃ until a uniform transparent solution is formed; 4) Doping and dispersion of MXene: MXene powder is weighed and added to the mixture of APC and PDES, and ultrasonic treatment is carried out for 30-45 minutes to make the MXene fully and uniformly dispersed in the system; 5) Solidification molding: the above-mentioned mixed solution is poured into a polytetrafluoroethylene mold, and placed in a vacuum drying box to dry at 70-100℃ to remove the solvent, and a conductive elastomer containing MXene is obtained.

[0010] In any embodiment, the synthesis of the aliphatic polycarbonate (APC) is as follows: the molar ratio of polyethylene glycol monomethyl ether mPEG113, 5-methyl-5-benzyloxycarbonyl trimethylene carbonate, 5-methyl-5-carboxyl trimethylene carbonate and stannous octoate is 1:50:25-50:1; polyethylene glycol monomethyl ether, 5-methyl-5-benzyloxycarbonyl trimethylene carbonate, 5-methyl-5-carboxyl trimethylene carbonate are placed in a polymerization tube, and a toluene solution of stannous octoate is added; vacuum is applied and then argon is filled, and the process is repeated several times; the polymerization tube is heated and sealed; the polymerization tube is placed in an oil bath at 110-150°C, and after the contents in the tube are completely melted, the system is mixed uniformly by repeatedly shaking the polymerization tube; after constant temperature reaction for 10-15 h, the polymerization tube is taken out and naturally cooled to room temperature, the product is dissolved with tetrahydrofuran, precipitated with methanol, and vacuum dried to obtain a colorless transparent product.

[0011] In any embodiment, the synthesis of the polydeep eutectic solvent (PDES) is as follows: choline chloride and acrylic acid with a molar ratio of 1:1-2 are weighed into a flask, the reaction system is heated and stirred in a constant temperature oil bath at 50-70°C for 3-5 h until the system becomes a homogeneous transparent liquid, obtaining a deep eutectic solvent (DES); 10 mL of the DES is taken, 0.5% of the DES mass of a photoinitiator 2959 is added, and the mixture is placed in a polytetrafluoroethylene mold; the mold is placed under a 365 nm ultraviolet lamp with a power of 550 W at a distance of 10 cm to initiate polymerization by light, and the light irradiation time is 2 minutes, obtaining a PDES gel.

[0012] In any embodiment, the choline chloride is vacuum dried at 60°C for 4 h, and the acrylic acid is dried by molecular sieves.

[0013] In any embodiment, the dissolution temperature in step 3) is 70°C.

[0014] In any embodiment, in step 4), 1-5 wt% of the total amount of APC and PDES is added to MXene powder.

[0015] In any embodiment, the reaction temperature in step 1) is controlled at 130°C, and the reaction time is controlled at 12 h.

[0016] In any embodiment, the mass ratio of APC / PDES in step 3) is 1:0.5-3.

[0017] In any embodiment, the doping mass of MXene in step 4) is 3-5 wt%.

[0018] The third aspect of the present application also provides an application of a polycarbonate-based conductive elastomer based on MXene doping. The above material is applied in flexible sensors, electronic skin, health monitoring, photothermal therapy and intelligent antibacterial materials.

[0019] The characteristics and benefits of the present application: Structural features and performance characteristics of the conductive elastomer of the present application: 1) Stable interface structure: The rich polar groups (-OH, =O, -F) on the surface of MXene form multiple hydrogen bonds with the carboxyl groups in APC or PDES, establishing a stable non-covalent network and improving the structural stability and swelling inhibition ability of the elastomer.

[0020] 2) Enhanced mechanical properties: With the increase of the doping ratio of MXene, the material fracture stress is increased from 175.4 kPa to 363.2 kPa, and the elastic modulus is improved, which is suitable for high-toughness deformation scenarios.

[0021] 3) Excellent sensing sensitivity: The material has high response sensitivity (GF up to 6.02) in the strain range of 1%-5%, which is suitable for wearable motion detection, human-computer interaction interface and other micro-deformation recognition scenarios.

[0022] 4) Significant light-heat conversion ability: MXene in the material converts 808 nm near-infrared light into heat energy through localized surface plasmon resonance, and the surface temperature is increased to 87.5℃ within 110 s of irradiation, providing a basis for subsequent antibacterial and thermal response applications.

[0023] 5) Light-heat antibacterial function: After near-infrared irradiation, the material has antibacterial rates of 99.93% and 99.80% against Gram-positive bacteria (Staphylococcus aureus) and Gram-negative bacteria (Escherichia coli), respectively, without the need for additional antibacterial agents to achieve high-efficiency sterilization.

[0024] Compared with the prior art, the multifunctional polycarbonate conductive elastomer based on MXene doping has the following benefits: 1) Simple preparation process, environmentally friendly, no need for high temperature and high pressure; 2) Excellent comprehensive performance, achieving multiple optimization of mechanical strength, electrical sensitivity, biocompatibility and biodegradability, light-heat response and antibacterial performance; 3) Stable structure, MXene is uniformly dispersed after doping, avoiding aggregation and sedimentation, ensuring long-term usability of the material; 4) Wide range of applications, which can be extended to fields such as flexible sensors, electronic skin, health monitoring, photothermal therapy and intelligent antibacterial materials.

[0025] The present application not only provides a new type of conductive elastomer material, but also establishes a functional material design and preparation path with high universality, low cost and high performance, which has significant theoretical value and application prospect. BRIEF DESCRIPTION OF DRAWINGS

[0026] Figure 1 Synthesis route of the MXene-doped polycarbonate-based conductive elastomer according to the present application; Figure 2 Infrared spectrogram of the MXene-doped conductive elastomer according to the present application Example 1-3; Figure 3 SEM image of the MXene-doped conductive elastomer according to the present application Example 1-3; Figure 4 Stress-strain curve of the MXene-doped conductive elastomer according to the present application Example 1-3; Figure 5 Norm factor comparison chart (a) and relative resistance-time response chart (b) of the DPM3 sample of the present application Example 3 under different strain ranges; Figure 6 ECG signal chart collected after the DPM3 sample of the present application Example 3 was attached to the wrist; Figure 7 Surface thermal imaging chart corresponding to the DPM3 sample of the present application Example 3 at different time points; Figure 8 Bacteriostatic effect chart of the DPM3 sample of the present application Example 3 under photo-thermal action, wherein a is the S. aureus blank group, b is the S. aureus control group, c is the S. aureus experimental group, d is the E. coli blank group, e is the E. coli control group, and f is the E. coli experimental group. DETAILED DESCRIPTION

[0027] Hereinafter, specific embodiments of the MXene-doped polycarbonate-based conductive elastomer and the preparation method thereof according to the present application are specifically disclosed with appropriate reference to the accompanying drawings. However, there will be cases where unnecessary detailed descriptions are omitted. For example, there will be cases where detailed descriptions of matters known to those skilled in the art, repeated descriptions of substantially identical structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate understanding by those skilled in the art. In addition, the accompanying drawings and the following description are provided so that those skilled in the art can fully understand the present application, and are not intended to limit the subject matter recited in the claims.

[0028] The ranges disclosed herein are intended to be "open" ranges, i.e., the upper and lower limits of the range are not included. The ranges are also intended to include any and all sub-ranges of the range, i.e., all combinations of any two of the range limits, unless otherwise indicated. For example, a range of "1 to 10" is intended to include any number from 1 to 10, including the integers 1 and 10. Unless otherwise indicated, the use of "or" in the disclosed aspects herein is the inclusive, and not the exclusive use. Only the context, and not the number of times an item is used, can determine that it is the exclusive use. For example, the phrase "A uses B or C" means that A can use B, or A can use C, or A can use both B and C. Also, the use of the term "one" or "a" or "the" is intended to be singular as well as plural, unless only the singular form is used. For example, the phrase "one or more of A, B, and C" means that A, B, or C can be present, and that one of A, B, and C can be present, and that two of A, B, and C can be present, and that all of A, B, and C can be present.

[0029] All embodiments and optional embodiments of the present application can be combined with each other to form new technical solutions, unless otherwise specified.

[0030] All technical features and optional technical features of the present application can be combined with each other to form new technical solutions, unless otherwise specified.

[0031] All steps of the present application can be performed in sequence or randomly, preferably in sequence, unless otherwise specified. For example, the method comprises steps (a) and (b), which means that the method can comprise steps (a) and (b) in sequence, or steps (b) and (a) in sequence. For example, the method can further comprise step (c), which means that step (c) can be added to the method in any order, for example, the method can comprise steps (a), (b) and (c), or steps (a), (c) and (b), or steps (c), (a) and (b), etc.

[0032] Unless otherwise specified, "including" and "including" mentioned in the present application means open, and can also be closed. For example, "including" and "including" can mean that other components not listed can also be included or contained, or only the listed components can be included or contained.

[0033] If not specifically stated, the term "or" in this application is inclusive. For example, the phrase "A or B" means "A, B, or both A and B." More specifically, any of the following satisfy the condition "A or B": A is true (or present) and B is false (or not present); A is false (or not present) and B is true (or present); or both A and B are true (or present).

[0034] Based on the mechanical properties, electrical response characteristics, biocompatibility, biodegradability and photothermal antibacterial function of the materials in this application, it is suitable for the requirements of wearable sensors field. Researchers try to introduce two-dimensional materials with high specific surface area, good electrical conductivity and interface activity as conductive fillers. MXene is a material composed of two-dimensional transition metal carbide, nitride or carbonitride, with the following characteristics: 1) excellent electrical conductivity: due to its two-dimensional structure and metal conduction band characteristics, MXene shows a conductivity close to the metal level, which is an excellent charge carrier transport medium; 2) high specific surface area and surface functional groups: there are a large number of polar functional groups (hydroxyl, carbonyl, fluorine group, etc.) on the surface of MXene sheet, which is conducive to the formation of hydrogen bonds and other non-covalent interactions with the polymer matrix, and improves the interface bonding strength; 3) excellent light-to-heat conversion ability: MXene material has strong absorption in the near-infrared region, and can realize high-efficiency light-to-heat conversion through local surface plasmon resonance.

[0035] Aliphatic polycarbonate (APC) has attracted much attention due to its good biocompatibility, biodegradability, and controllable mechanical properties. Aliphatic polycarbonates are usually prepared by ring-opening polymerization of cyclic carbonate monomers. This polymerization method has the advantages of mild reaction conditions and controllable product structure. Aliphatic polycarbonates have many excellent properties, making them have wide application prospects in the field of materials science. On the one hand, they have good biocompatibility, making them applicable in the field of biomedicine; on the other hand, aliphatic polycarbonates have certain flexibility and processability.

[0036] As a new type of green ionic liquid, deep eutectic solvent (DES) not only has the advantages of wide source, low cost, easy preparation, antibacterial, biodegradable and so on, but also has high design freedom, wide temperature resistance, good ion conductivity and chemical stability, which makes up for the shortcomings of hydrogel (easy to freeze at low temperature, easy to volatilize at high temperature) and conventional ionic liquid (high cost, certain toxicity). The core feature of DES is to build a dynamic hydrogen bond network through hydrogen bond acceptors (such as polyols, carboxylic acids, etc.) and hydrogen bond donors (such as quaternary ammonium salts, etc.). However, since DES can also play a certain toughening role in gel, which makes the mechanical properties of most DES-based ionic gels relatively weak. The application uses EDS polymer (PDES, which is an elastomer) to improve the mechanical properties, and building an ionic gel with good mechanical properties is a feasible way. Further adding MXene is to enhance the conductivity and sensing performance of the elastomer, improve the problem of PDES reducing ion transmission capacity, and also has photo-thermal effect.

[0037] Through a large number of research and experimental verification, the inventors of the present application dissolve APC and PDES in a suitable solvent, mix thoroughly, and then dope different contents of MXene by ultrasonic dispersion method to construct a multifunctional conductive elastomer with good stretchability, high sensitivity responsiveness, biocompatibility and photo-thermal antibacterial effect. The formation of the conductive elastomer is realized by the stable cross-linking network formed by the rich multiple hydrogen bonds and other interactions among APC, PDES and MXene, which realizes the uniform distribution of MXene in the elastomer system and the non-covalent interface stability, significantly improves the mechanical properties, electrical properties and photo-thermal properties of the material, and has important application prospects in the fields of personal motion monitoring, intelligent health care and human-computer interaction.

[0038] In one embodiment of the present application, a polycarbonate-based conductive elastomer doped with MXene is provided, which comprises aliphatic polycarbonate, deep eutectic solvent and MXene, the mass ratio of the aliphatic polycarbonate and the deep eutectic solvent is 1:0.5-3, and the addition amount of the MXene is 1-5 wt% of the total mass of APC and PDES.

[0039] In some embodiments, the aliphatic polycarbonate is prepared from the following raw materials: polyethylene glycol monomethyl ether, 5-methyl-5-benzyloxycarbonyl trimethylene carbonate, 5-methyl-5-carboxyl trimethylene carbonate and stannous octoate, and the amount-of-substance ratio is 1:50:25-50:1.

[0040] Polycarbonates with different mechanical properties are obtained.

[0041] In some embodiments, the polydeep eutectic solvent is prepared from raw materials in a molar ratio of 1:1-2 of choline chloride to acrylic acid.

[0042] Choline chloride (ChCl) and malonic acid (AA) can be used to prepare a deep eutectic solvent, which is composed of a hydrogen bond donor (ChCl) and a hydrogen bond acceptor (AA) in a certain ratio. By adjusting the ratio of monomers, the electrical conductivity and mechanical properties of the polydeep eutectic solvent can be optimized. Within this range, the electrical conductivity and mechanical properties of the PDES are optimal.

[0043] In one embodiment of the present application, a preparation method of a MXene-doped polycarbonate-based conductive elastomer is provided, which comprises the following steps: 1) Synthesis of aliphatic polycarbonate; 2) Synthesis of polydeep eutectic solvent; 3) Pre-mixing and dissolving: weigh APC and PDES, and add them to N,N-dimethylformamide in a mass ratio of 1:0.5-3, and magnetically stir at 50-100°C until a uniform transparent solution is formed; N,N-dimethylformamide (DMF) is used as the solvent, and the addition of DMF can ensure uniform mixing of the components; finally, remove the DMF under vacuum to obtain the elastomer.

[0044] A low content of PDES affects the electrical conductivity, and a high content affects the uniformity of mixing, which in turn affects the mechanical properties, electrical conductivity, and other properties.

[0045] 4) Doping and dispersion of MXene: weigh the MXene powder and add it to the mixture of APC and PDES, and use ultrasonic treatment for 30-45 minutes to ensure that the MXene is uniformly dispersed in the system; MXene is a nano-powder.

[0046] 5) Curing and molding: pour the above-mentioned mixed solution into a polytetrafluoroethylene mold, and place it in a vacuum drying oven to remove the solvent at 70-100°C, thereby obtaining a MXene-containing conductive elastomer. High drying temperature can cause bubbles in the elastomer film, which in turn affects the material properties.

[0047] In some embodiments, the synthesis of the aliphatic polycarbonate (APC): the molar ratio of polyethylene glycol monomethyl ether mPEG113, 5-methyl-5-benzyloxycarbonyl trimethylene carbonate, 5-methyl-5-carboxyl trimethylene carbonate and stannous octoate is 1:50:25-50:1, polyethylene glycol monomethyl ether mPEG113, 5-methyl-5-benzyloxycarbonyl trimethylene carbonate, 5-methyl-5-carboxyl trimethylene carbonate are placed in a polymerization tube, 250 µL of stannous octoate toluene solution is added; vacuum is applied and then argon is filled, the process is repeated several times, and the polymerization tube is heated and sealed; the polymerization tube is placed in an oil bath at 110-150℃, and after the contents in the tube are completely melted, the polymerization tube is repeatedly shaken to mix the system uniformly; after constant temperature reaction for 10-15 h, the polymerization tube is taken out and naturally cooled to room temperature, the product is dissolved with tetrahydrofuran, precipitated with methanol, and vacuum dried to obtain a colorless transparent product.

[0048] In some embodiments, the synthesis of the polydeep eutectic solvent (PDES): choline chloride and acrylic acid with a molar ratio of 1:1-2 are weighed into a flask, the reaction system is heated and stirred in a constant temperature oil bath at 50-70℃ for 3-5 h until the system becomes a uniform transparent liquid, obtaining a deep eutectic solvent (DES); a certain amount of DES is taken, 0.5% of the mass of the DES of photoinitiator 2959 is added, and the mixture is placed in a polytetrafluoroethylene mold, the mold is placed under a 365 nm ultraviolet lamp with a power of 550 W at a distance of 10 cm to initiate polymerization by light, and the light irradiation time is 2 minutes, obtaining a PDES gel.

[0049] In some embodiments, the choline chloride is vacuum dried at 60℃ for 4 h, and the acrylic acid is dried by molecular sieves.

[0050] In some embodiments, the dissolution temperature in step 3) is 70℃.

[0051] The solution is formed slowly below 70℃, and above 70℃, there is also a certain safety hazard in energy consumption, and the application optimizes to improve the preparation quality and efficiency of the product.

[0052] In some embodiments, in step 4), 1-5 wt% of the total amount of APC and PDES is added to MXene powder.

[0053] MXene (Ti3C2T X ) powder is born by etching MAX phase with hydrogen fluoride, and Tx represents the presence of surface functional groups, which can be hydrogen, oxygen, hydroxyl or other functional groups.

[0054] When the amount of MXene added is too small, the electrical conductivity, sensing sensitivity and photothermal performance of the corresponding material are not ideal; when the amount added exceeds 5%, the MXene is not uniformly dispersed in the elastomer and agglomerates.

[0055] In some embodiments, the reaction temperature of step 1) is controlled at 130 ℃, and the reaction time is controlled at 12 h. This is the optimal preparation condition, with high preparation efficiency and good product quality.

[0056] In some embodiments, the mass ratio of APC / PDES in step 3) is 1:0.5-3.

[0057] In some embodiments, the doping mass of MXene in step 4) is 3-5 wt%.

[0058] Examples Hereinafter, examples of the present application will be described. The examples described below are exemplary and are for the purpose of explanation of the present application only, and should not be construed as limiting the present application. In the examples, specific techniques or conditions not mentioned are performed according to the techniques or conditions described in the literature in the art or according to the product manual. The reagents or instruments not mentioned by the manufacturer are all conventional products that can be obtained commercially.

[0059] Example 1 A polycarbonate-based conductive elastomer based on MXene doping and a preparation method thereof, comprising the following steps: 1) Synthesis of aliphatic polycarbonate (APC) 0.95 g (0.5 mmol) of polyethylene glycol monomethyl ether mPEG 113 , 6.25 g (25 mmol) of 5-methyl-5-benzyloxycarbonyl trimethylene carbonate (laboratory self-made), 2.0 g (12.5 mmol) of 5-methyl-5-carboxyl trimethylene carbonate (laboratory self-made) were weighed into a polymerization tube, and 350 μL of stannous octoate toluene solution (0.2062 mol / L) was added. After vacuumizing and recharging with argon for 3 times, the polymerization tube was heated and sealed. The polymerization tube was placed in a 130℃ oil bath, and after the contents in the tube were completely melted, the polymerization tube was repeatedly shaken to mix the system uniformly. After constant temperature reaction for 12 h, the polymerization tube was taken out and naturally cooled to room temperature, the product was dissolved with tetrahydrofuran, precipitated with methanol, and vacuum dried to obtain a colorless transparent product.

[0060] 2) Synthesis of polydeep eutectic solvent (PDES) Take 13.96 g (0.1 mol) of dry choline chloride and 12.96 g (0.18 mmol) of acrylic acid into a flask, heat and stir the reaction system in a 60°C constant temperature oil bath for 4 h until the system becomes a homogeneous transparent liquid, obtaining a deep eutectic solvent (DES). Take 10 mL of DES, add 0.5% of the DES mass photoinitiator 2959, place it in a polytetrafluoroethylene mold, and place the mold under a 365 nm ultraviolet lamp with a power of 550 W at a distance of 10 cm to initiate polymerization by light. The light irradiation time is 2 minutes, and a PDES gel is obtained.

[0061] 3) Pre-mixing and dissolving Take APC and PDES according to the mass ratio of 1:2 and add them to 10 mL of N,N-dimethylformamide. Stir magnetically at 70°C until a transparent solution is formed.

[0062] 4) Solidification molding Take 1 wt% MXene (Ti3C2T X ) powder and add it to the mixture of APC and PDES. Use ultrasonic treatment for 30 minutes to make the MXene fully and uniformly dispersed in the system. Pour the solution into a polytetrafluoroethylene mold and vacuum dry it at 80°C to obtain a conductive elastomer containing MXene.

[0063] Example 2 Compared with Example 1, the difference is in step 4) solidification molding: take 2 wt% MXene (Ti3C2T x ) powder and add it to the mixture of APC and PDES. Use ultrasonic treatment for 30 minutes to make the MXene fully and uniformly dispersed in the system. Pour the solution into a polytetrafluoroethylene mold and vacuum dry it at 80°C to obtain a conductive elastomer containing MXene.

[0064] Example 3 Compared with Example 1, the difference is in step 4) solidification molding: take 3 wt% MXene (Ti3C2T x ) powder and add it to the mixture of APC and PDES. Use ultrasonic treatment for 30 minutes to make the MXene fully and uniformly dispersed in the system. Pour the solution into a polytetrafluoroethylene mold and vacuum dry it at 80°C to obtain a conductive elastomer containing MXene.

[0065] Example 4 Compared with Example 1, the difference is in step 4) solidification molding: take 4 wt% MXene (Ti3C2T x) powder was added to the mixed solution of APC and PDES, and ultrasonic treatment was performed for 30 minutes to make MXene fully and uniformly dispersed in the system. The solution was poured into a polytetrafluoroethylene mold and vacuum dried at 80°C to obtain a conductive elastomer containing MXene.

[0066] Example 5 Compared with Example 1, the difference lies in step 4) curing molding: 5 wt% MXene (Ti3C2T x ) powder was added to the mixed solution of APC and PDES, and ultrasonic treatment was performed for 30 minutes to make MXene fully and uniformly dispersed in the system. The solution was poured into a polytetrafluoroethylene mold and vacuum dried at 80°C to obtain a conductive elastomer containing MXene.

[0067] The following instruments and characterization methods were used to analyze the examples: (1) Infrared spectroscopy: FT-IR test was performed using Spectrumho Fourier Transform Infrared Spectrometer of American PerkinElmerg Company, and the wave number range of absorption spectrum scanning was 4000-500 cm -1 .

[0068] (2) Scanning electron microscope: scanning electron microscope test was performed using SU8010 scanning electron microscope of HITACHI Company. After gold spraying treatment of the sample, the surface morphology of the conductive elastomer was observed and recorded under an acceleration voltage of 5 kV and a current of 10 μA.

[0069] (3) Mechanical property test: CMT6103 electronic universal testing machine of Metzler industrial system was used, and the sample was prepared by dumbbell-shaped polytetrafluoroethylene mold with a size of national standard I, the tensile rate was 50 mm min -1 , and the stress-strain curve of the material was obtained with stress as Y axis and strain as X axis.

[0070] (4) Sensing performance test: CHI760E electrochemical workstation of Shanghai Chenhua Instrument Co., Ltd. was used for test. When detecting the conductive performance and sensing performance of the elastomer sample, the elastomer was prepared into a size of 30 mm x 15 mm x 3 mm by polytetrafluoroethylene mold, and the two ends were fixed by double-headed alligator clip electrodes, and the other end of the alligator clip electrode was connected with the electrochemical workstation. The strain current change of the elastomer was recorded by selecting i-t mode, and the strain sensing signal was represented by relative resistance change ). The resistance was calculated by the following formula.

[0071] (1) wherein the voltage applied to the electrochemical station, the current of the elastomer.

[0072] The relative resistance change is calculated by the following formula.

[0073] (2) wherein the resistance value of the elastomer when a strain is applied, the initial resistance value of the elastomer.

[0074] The sensitivity of the flexible sensor assembled by the conductive elastomer is usually measured by a specification factor (Sf) which can be calculated by the following formula.

[0075] (3) wherein the relative resistance change, the strain applied to the elastomer, including the applied force, etc.

[0076] (5) Photo-thermal performance test: the conductive elastomer samples (sample size: 20 mm x 20 mm x 15 mm) with different MXene doping contents were irradiated by an 808 nm near-infrared light emitter (1 W cm -2 ) of HW808AD1000-34F type of Shenzhen Infrared Laser Technology Co., Ltd. The temperature of the samples after starting the irradiation was recorded in real time by a HD46E15 type handheld temperature measurement thermal imager of Huajing Kangguang Optoelectronics Co., Ltd.

[0077] The chemical reagents used in the embodiments of the present application are provided by the National Pharmaceutical Group Chemical Reagent Co., Ltd. The present application will be described in detail below in conjunction with specific examples. These examples are only used to illustrate the present application and are not used to limit the application scope of the present application. Various modifications or modifications of the present application and the like are also within the scope limited by the claims attached to the present application.

[0078] Figure 2 The infrared spectra of the conductive elastomers based on MXene doping described in examples 1-3, DPM1, DPM2, DPM3 correspond to the samples obtained in examples 1-3, respectively. The absorption peak at 3400 cm -1 belongs to the stretching vibration peak of O-H, the absorption peak at 1735 cm -1 belongs to the stretching vibration peak of C=O, 1608 cm -1 belongs to the benzene ring skeleton vibration peak, 1340 cm -1 ​C-N stretching vibration peak belonging to quaternary ammonium salt in choline chloride. With the increase of MXene material doping content, the absorption peak of O-H shifts from 3381 cm -1 to 3371 cm -1 , and the peak position of C=O stretching vibration peak also shifts from 1732 cm -1 to 1724 cm -1 , which confirms that the hydrogen bond is formed between the surface groups of MXene material and the carbonyl groups in the elastomer system.

[0079] Figure 3 SEM images of the MXene doped conductive elastomers described in Examples 1-3, wherein a, b, c correspond to the SEM images of the conductive elastomers of Example 1, Example 2, and Example 3, respectively. With the increase of MXene doping content, the number of sheet-like materials on the surface of the conductive elastomer increases, and still presents a more uniform state of embedding on the surface of the conductive elastomer without aggregation phenomenon, indicating that the MXene material has good dispersibility in the conductive elastomer.

[0080] Figure 4 Stress-strain curve of the MXene doped conductive elastomers described in Examples 1-3. With the increase of MXene doping content from 1 wt% to 3 wt%, the crosslinking density of the crosslinking network further increases, and the strength of the conductive elastomer also increases, and the breaking stress increases from 175.35 kPa to 363.22 kPa. DPM1, DPM2, DPM3 represent the samples obtained in Example 1, Example 2, and Example 3, respectively.

[0081] Figure 5 The gauge factor comparison chart and the relative resistance-time response chart of the DPM3 sample described in Example 3 under different strain ranges. In the range of 0-300%, the conductive elastomer can form an effective and repeatable response to strain, and the gauge factor increases from 3.72 to 6.02 with the expansion of the strain range, indicating that it has high sensitivity.

[0082] Figure 6 The electrocardiogram recorded by the DPM3 electrode patch described in Example 3 attached to the wrist of the test subject. The electrocardiogram recorded by the DPM3 electrode patch attached to the wrist of the test subject shows regular signal output and good sensitivity.

[0083] Figure 7 The surface thermal imaging chart of the DPM3 sample described in Example 3 at different time points. With the increase of illumination time, the surface temperature of the conductive elastomer gradually increases, and the surface temperature of the DPM3 conductive elastomer increases from 25.3°C to 87.5°C after 110 s of near-infrared light source irradiation.

[0084] Figure 8 The antibacterial effect diagram of the DPM3 sample described in Example 3 under the action of photothermal. Figure 8 a The number of S. aureus colonies in the blank group was 1411, Figure 8 b The number of S. aureus colonies in the control group was 1435, Figure 8 c The number of S. aureus colonies in the experimental group was 1, and the antibacterial activity of the conductive elastomer DPM3 on S. aureus was 99.93%; Figure 8 d The number of E. coli colonies in the blank group was 1033, Figure 8 e The number of E. coli colonies in the control group was 1014, Figure 8 f The number of E. coli colonies in the experimental group was 2, and the antibacterial activity of the conductive elastomer on E. coli was 99.80%. The conductive elastomer DPM3 doped with MXene material has a strong photothermal inhibition effect on the growth of S. aureus and E. coli. Among them, the blank group is not treated; the control group only places the bacterial diluent in the twelve-hole plate under the same light conditions as the experimental group; the experimental group places the bacterial diluent on the DPM3 conductive elastomer prepared in advance in the twelve-hole plate, and the light condition is under the 808 nm near-infrared light source (1 W m -2 ) to make the light spot diameter of the guide light source on the material fixed at 10 mm, and irradiated for 10 min.

[0085] As can be known from the description of the above specific embodiments, the MXene-doped conductive elastomer provided by the application has a simple preparation process, excellent material performance, and significant advantages in mechanical strength, sensing response, photothermal conversion, and antibacterial effect, and has important application prospects in the fields of human motion monitoring, health monitoring, rehabilitation treatment, etc.

[0086] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and embodiments having the same technical idea and playing the same role and effect within the scope of the technical solutions of the present application are all included in the technical scope of the present application. In addition, within the scope of the main idea of the present application, various modifications of the embodiments, combination of part of the components in the embodiments to construct other ways, which can be thought of by those skilled in the art, are also included in the scope of the present application.

Claims

1. A polycarbonate-based conductive elastomer based on MXene doping, characterized in that, It includes aliphatic polycarbonate, polyeutectic solvent and MXene, wherein the mass ratio of aliphatic polycarbonate and polyeutectic solvent is 1:0.5-3, and the amount of MXene added is 1-5 wt% of the total mass of aliphatic polycarbonate and polyeutectic solvent.

2. The conductive elastomer according to claim 1, characterized in that, The aliphatic polycarbonate is prepared from the following raw materials: polyethylene glycol monomethyl ether, 5-methyl-5-benzyloxycarbonyltrimethylene carbonate, and 5-methyl-5-carboxylic acid stannous octoate in a molar ratio of 1:50:25-50:

1.

3. The conductive elastomer according to claim 1, characterized in that, The polyeutectic solvent is prepared from the following raw materials: the molar ratio of choline chloride to acrylic acid is 1:1-2.

4. A method for preparing MXene-doped polycarbonate conductive elastomers, characterized in that, Includes the following steps: 1) Synthetic aliphatic polycarbonates; 2) Synthesize polyeutectic solvents; 3) Premixing and dissolving: Weigh aliphatic polycarbonate and polyeutectic solvent, add them to N,N-dimethylformamide at a mass ratio of 1:0.5-3, and stir magnetically at 50-100℃ until a homogeneous and transparent solution is formed; 4) Doping and dispersion of MXene: Weigh 1-5 wt% of MXene powder of aliphatic polycarbonate and polyeutectic solvent, add it to the mixture of aliphatic polycarbonate and polyeutectic solvent, and use ultrasonic treatment for 30-45 minutes to make MXene fully and uniformly dispersed in the system. 5) Curing and molding: Pour the mixed solution obtained in step 4) into a polytetrafluoroethylene mold, place it in a vacuum drying oven, and dry it at 70-100℃ to remove the solvent, thereby obtaining a conductive elastomer containing MXene.

5. The preparation method according to claim 4, characterized in that, Synthesis of the aliphatic polycarbonate: Polyethylene glycol monomethyl ether, 5-methyl-5-benzyloxycarbonyltrimethylene carbonate, 5-methyl-5-carboxylic acid trimethylene carbonate, and stannous octoate were weighed in a molar ratio of 1:50:25-50:

1. These components were placed in a polymerization tube, and a toluene solution of stannous octoate was added. The tube was then evacuated and purged with argon gas, repeated several times, and then heated and sealed. The polymerization tube was placed in an oil bath at 110-150℃. After all the substances in the tube had melted, the tube was repeatedly shaken to ensure uniform mixing. After reacting at a constant temperature for 10-15 h, the polymerization tube was removed and allowed to cool naturally to room temperature. The product was dissolved in tetrahydrofuran, precipitated with methanol, and dried under vacuum to obtain a colorless and transparent product.

6. The preparation method according to claim 4, characterized in that, Synthesis of the deep eutectic solvent: Choline chloride and acrylic acid in a molar ratio of 1:1-2 were weighed and added to a flask. The reaction system was heated and stirred in a constant temperature oil bath at 50-70℃ for 3-5 hours until the system became a homogeneous and transparent liquid, which was then obtained as the deep eutectic solvent (DES). 10 mL of DES was taken and 0.5% of the DES mass of photoinitiator was added. The mixture was placed in a polytetrafluoroethylene mold and the mold was placed at a distance of 10 cm under a 365 nm UV lamp with a power of 550W for 2 minutes to initiate polymerization, thereby obtaining the deep eutectic solvent gel.

7. The preparation method according to claim 4, characterized in that, The dissolution temperature in step 3) is 70℃.

8. The preparation method according to claim 4, characterized in that, In step 1), the reaction temperature is controlled at 130℃ and the reaction time is controlled at 12h.

9. The preparation method according to claim 4, characterized in that, In step 4), the doping mass of MXene is 3-5 wt%.

10. The application of MXene-doped polycarbonate conductive elastomers, characterized in that, The conductive elastomers included in any one of claims 1-3 or the conductive elastomers prepared by the method of any one of claims 4-9 are used in flexible sensors, electronic skin, health monitoring, photothermal therapy and smart antibacterial materials.

Citation Information

Patent Citations

  • Polycarbonate blending material with cold resistance conduction effect and preparation method thereof

    CN108912645A

  • Amphiphilic poly (trimethylene carbonate) as well as preparation method and application thereof

    CN110790911A

  • Expansion type rapid drug release nano-drug carrier based on amphiphilic polycarbonate and preparation method of expansion type rapid drug release nano-drug carrier

    CN115093556A

  • Carbon filler and MXene material reinforced polymer composite material as well as preparation method and application thereof

    CN118344722A

  • Preparation method and application of polymerizable eutectic gel conductive elastomer based on supramolecular crosslinking

    CN119019800A